2013
DOI: 10.4028/www.scientific.net/msf.738-739.496
|View full text |Cite
|
Sign up to set email alerts
|

Shape Memory Properties of Ultrafine-Grained Austenitic Stainless Steel

Abstract: In this work the effect of grain refinement on the shape memory properties of a Fe-Mn-Si-Cr-Ni-Co-Ti alloy was evaluated using compression tests. In order to refine the microstructure, the samples were heavily deformed by equal channel angular extrusion (ECAE) and then annealed at different temperatures ranging from 450°C to 1050°C. These treatments resulted in the formation of intermetallic precipitates and strengthening of austenitic matrix. The results of compression testes show that the higher degrees of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…However, the results of our previous work 12 indicated a different interpretation for the effect of matrix strengthening on the shape memory effect. It was observed that the Equal Channel Angular Extrusion (ECAE), followed by annealing treatments in temperatures ranging from 650ºC to 850ºC, significantly increased the mechanical resistance of the stainless Fe-Mn-Si-Cr-Ni-Co-Ti shape memory steel, owing to grain refinement and the precipitation of second-phase particles.…”
Section: Introductionmentioning
confidence: 58%
“…However, the results of our previous work 12 indicated a different interpretation for the effect of matrix strengthening on the shape memory effect. It was observed that the Equal Channel Angular Extrusion (ECAE), followed by annealing treatments in temperatures ranging from 650ºC to 850ºC, significantly increased the mechanical resistance of the stainless Fe-Mn-Si-Cr-Ni-Co-Ti shape memory steel, owing to grain refinement and the precipitation of second-phase particles.…”
Section: Introductionmentioning
confidence: 58%
“…However, the increase of the annealing temperature to 400 °C promoted an increment in hardness values (262 ± 13 HV), possibly due to precipitation of Ti 3 Ni 4 1,2,17 , followed by a decrease (200 ± 21 HV) in the further annealing treatment at 500 °C/1h. At 400 °C, the metastable phase Ti 3 Ni 4 is formed in lower annealing temperature consists of thin plates coherent with the matrix increase the resistance of B2 2,8 .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding thermo-mechanical processing, equalchannel angular extrusion 3 has been successfully applied to modify some properties of the shape memory materials [4][5][6][7] . Using ECAE process [8][9][10][11][12][13][14][15][16] , some studies have been done in NiTi SMA with respect to microstructural characteristics related to the change of the direct (B2→B19') martensitic transformation to intermediate B2→R martensitic transformation.…”
Section: Introductionmentioning
confidence: 99%
“…The authors attributed these results to a low strength of austenitic matrix with a microstructure free of complex defects and consisting of equiaxed grains. Recently, Kafer et al 12 studied the effect of severe plastic deformation (introduced by ECAE processing) and heat treatment on stainless Fe-Mn-Cr-Ni-Co-Ti shape memory steel, separated the TSR in two parts as ESR and SR concluding that while the matrix hardness is low the major contribution to TSR comes from SR on heating as shown previously by Otubo et al 11 and as the matrix hardness starts to increase, the shape recovery due to ESR also starts to increase surpassing the SR. In order to evaluate the effect of microstructure on the total shape recovery (TSR), elastic shape recovery (ESR) and shape recovery (SR) on heating, stainless Fe-8Mn-5Si-13Cr-6Ni-12Co shape memory steel was processed by wire drawing and heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…These steels have the capacity to recover its original shape by the reverse transformation of stress induced ε martensite [1][2][3][4] . Some factors that influence in the capacity of shape memory recovery have been studied, such as the amount of pre-strain, thermomechanical training, alloying elements, deformation temperature and annealing temperature [5][6][7][8][9][10][11][12] . According to Akhondzadeh et al 5 , the annealing temperature is the more effective parameter to control the shape memory effect due to microstructural changes developed in the parent phase, influencing directly the reverse martensitic transformation.…”
Section: Introductionmentioning
confidence: 99%